An Experimental Organization of Precarious Professionals: The Two-Step Unionization of Québec Archaeologists - MacDonald, Ian; Kolhatkar, Manek (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2021)
This article discusses the sector-wide organization of contractual archaeologists in Québec, beginning with the formation of a workers’ committee and leading subsequently to union accreditation. We theorize the difficulty of organizing these “precarious professionals” and suggest that self-organization outside of an industrial relations framework may be required to overcome barriers to their unionization. Deliberation, norm setting, and informal parlays with employers lead to clarifying class distinctions that professional identification often occludes, while self-organization increases worker confidence in collective action.